2022
DOI: 10.1001/jamaoto.2021.3387
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Test Accuracy of Ultrasonography vs Computed Tomography for Papillary Thyroid Cancer Cervical Lymph Node Metastasis

Abstract: The use of ultrasonography (US) vs cross-sectional imaging for preoperative evaluation of papillary thyroid cancer is debated.OBJECTIVE To compare thyroid US and computed tomography (CT) in the preoperative evaluation of papillary thyroid cancer for cervical lymph node metastasis (CLNM), as well as extrathyroidal disease extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 73 publications
(92 reference statements)
0
23
0
Order By: Relevance
“…Currently, imaging examinations (mainly B ultrasound and computed tomography) and cytology pathology are the main means of preoperative evaluation of cervical lymph nodes in PTC patients. However, the sensitivity of the methods is mostly below 70% (13,14). Accordingly, these preoperative examinations may not provide sufficient evidence for surgical decisions in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, imaging examinations (mainly B ultrasound and computed tomography) and cytology pathology are the main means of preoperative evaluation of cervical lymph nodes in PTC patients. However, the sensitivity of the methods is mostly below 70% (13,14). Accordingly, these preoperative examinations may not provide sufficient evidence for surgical decisions in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…While subsequent sub-group analyses for central and lateral compartment LNM in our study is warranted, we found that further sub-stratification limited the patient cohorts significantly. Since LNM is an important independent predictor of patient prognosis, several studies have suggested adjunct imaging modalities, such as computed tomography (CT), to help improve the low sensitivity often seen in US to minimize the missed detection of true positives [ 46 , 47 ]. Though prophylactic lymph node dissection during thyroidectomy has been debated [ 48 , 49 , 50 , 51 ], complete and thorough surgical resection can positively affect patient survival [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its sensitivity is low, resulting in some falsenegative rates. As reported, the diagnostic sensitivity of ultrasound to cervical LNM is only about 20% to 40% (9,10). Hence, occult LNM has been reported to occur in about 27% to 55% of PTC patients with cN0 neck (11,12).…”
Section: Introductionmentioning
confidence: 87%